2019
DOI: 10.3390/molecules24203637
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High-Intensity Ultrasound Pretreatment on Structure, Properties, and Enzymolysis of Soy Protein Isolate

Abstract: The objective of this study was to investigate the effects of different high-intensity ultrasonication (HIU) pretreatment on the structure and properties of soybean protein isolate (SPI) as well as enzymatic hydrolysis of SPI by bromelain and antioxidant activity of hydrolysates. The HIU-treated SPI fractions showed a decrease in the proportion of α-helices and β-turns and an increase in the content of β-sheets and random coils based on Fourier-transform infrared spectroscopy. Near-infrared spectra and fluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 46 publications
(78 reference statements)
2
39
0
Order By: Relevance
“…The degree of hydrolysis (DH) value was used to evaluate the extent of enzymatic proteolysis, as it is closely related to functional properties of protein hydrolysates. It was found high DH of protein hydrolysates could have the potential to enhance the antioxidant activities and surface hydrophobicity [6] , [14] , [34] . Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The degree of hydrolysis (DH) value was used to evaluate the extent of enzymatic proteolysis, as it is closely related to functional properties of protein hydrolysates. It was found high DH of protein hydrolysates could have the potential to enhance the antioxidant activities and surface hydrophobicity [6] , [14] , [34] . Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The OH-RSA was performed based on the slightly adjusted procedure of Zhao et al [6] . 1 mL of sample was mixed with 1 mL 3 mM FeSO 4 and 1.0 mL 3 mM H 2 O 2 and the mixture was kept at 25 °C (10 min) to react.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 4, the FTIR spectra of the TSPCs within the range of 400–4000 cm −1 showed that the characteristic adsorption band was similar to those observed in the proteins that were isolated from tilapia and soybean. It is worth noting that the amide A band, amide B band, amide I band, amide II band, amide III band, and several adsorption peak areas (400–800 cm −1 ) are the characteristic group frequencies that are produced by the repetitive polypeptide units of proteins [46]. The absorption band of the TSPCs at the amide A band was attributed to the stretching of N-H, and the amide B band was attributed to changes in the C-H stretching.…”
Section: Resultsmentioning
confidence: 99%
“…In the traditional tofu production process, different coagulants were appropriately added or the operation of several processes was changed or some technical methods were introduced to optimize the quality of the tofu products. Because the functional characteristics of tofu are related to the degree of denaturation and aggregation of soy proteins, the question of using SPI directly has been a more recent focus (Nishinari et al, 2014), SPI denaturation could be induced using ultrasound and HP techniques (Esteghlal et al, 2019;Zhao, Liu, Ding, Dong, & Wang, 2019), and it may be beneficial to explore the application of these F I G U R E 6 Different soy-based products and their pathway of production using modern processing. Adapted from Bennetau-Pelissero 2019technologies to further clarify their impact on the quality of tofu.…”
Section: Production Technologymentioning
confidence: 99%